Acute Effects of Resistance Training with Local Vibration - Couto, B. P.; Silva, H. R.; Filho, A. G.; da Silveira Neves, S. R.; Ramos, M. G.; Szmuchrowski, L. A.; Barbosa, M. P. (International Journal of Sports Medicine, 2013)
The aim of this study was to verify the acute effects of the application of local vibration on upper limbs during resistance training on the number of maximum repetitions, metabolic and hormonal responses. 32 volunteers performed a maximum voluntary contraction test during a lat pulldown exercise. After the test, all volunteers underwent one conventional resistance training session and one resistance training session with local vibration. In both interventions, volunteers performed 4 sets with the highest possible number of repetitions of the lat pulldown exercise at 55% of maximum voluntary contraction. During the vibratory resistance training intervention, vibration was locally applied (20-Hz and 12-mm). During the conventional resistance training, volunteers performed the same procedures without vibration. Blood samples were taken at each experimental session before and 5 min after the end of each intervention. No significant differences were observed in number of maximum repetitions between the series of vibratory and conventional training. Serum testosterone, cortisol and lactate were significantly increased after 2 interventions. Vibratory resistance training induced greater increases in testosterone and lactate concentrations. No significant changes were found in creatine kinase, creatinine or urea concentration. These data indicate that local vibration increases the metabolic and anabolic response to the resistance training, without changing the training volume.
Keywords: vibration exercise; strength training; muscle strength